Deltamethrin- and spinosad-mediated survival, activity and avoidance of the grain weevils Sitophilus granarius and S. zeamais. (December 2017) - Vélez, M.; Barbosa, W.F.; Quintero, J.; Chediak, M.; Guedes, R.N.C.
Abstract: The granary and maize weevils are serious worldwide threats to stored products and their control has heavily relied on synthetic insecticides, which are largely recommended based on studies with acute lethal doses neglecting the importance of potential sublethal effects of insecticides. Deltamethrin has been widely used for managing grain weevils and other stored grain pest species, but reported control failures with this insecticide sparked the search for alternative insecticidal compounds. The bioinsecticide spinosad is one of such alternatives whose use against stored grain insect pests is relatively recent, but encompasses the control of grain weevils. Nonetheless, little is known about the sublethal effects of spinosad on these insect pest species. Here we assessed the insecticidal effects of commercial formulations of spinosad and deltamethrin against the weevil species Sitophilus granarius and S. zeamais . Both spinosad and deltamethrin were able to effectively control the insects, although the latter caused a faster mortality than the former. Behavioral pattern changes were caused by both insecticides, especially deltamethrin, triggering irritability (i.e., avoidance after contact). Different feeding and drinking responses were also detected for both weevil species, which exhibited significant avoidance to deltamethrin and to spinosad, but with a milder response to the latter. Apparently spinosad is not as easily recognizable as deltamethrin by S. zeamais and S. granarius, remaining effective against both species without minimizing as much the potential exposure as deltamethrin. Highlights: Deltamethrin and spinosad compromise survival of Sitophilus granarius and S. zeamais . Both insecticides elicit behavioral response in adults of these weevil species. Deltamethrin exhibits faster activity achieving high mortality within hours. Deltamethrin also elicit significantly higher behavioral avoidance than spinosad. Spinosad is more likely to favor exposure favoring its effectiveness than deltamethrin.